(untitled) (Interdisciplinary Research in Education, 2022)
This article emphasizes looking for social justice in school pedagogies and practices to welcome students coming from other than the mainstream cultural background. The article utilizes the qualitative research design under which the narrative interview was carried outwith a single student coming from an ethnic minority background in one of the rural schools situated in the Kathmandu district. The goal was to explore their experiences about the mainstream school’s practices in which Nepali language as a medium of instruction, uniformed pedagogy, and centralized curriculum are the dominant approach. To understand the experiences of children with diverse socio-cultural backgrounds, the article employs the multicultural perspective as a lens.The article argues that most of the classroom management, teachers’ teaching skills and manners, school culture, and subject matters in the curricula and text are the most unwelcoming aspects to welcome children coming from different socio-cultural, linguistic, and ethnic backgrounds. The article explores many unexplored areas that concern the several gaps between entire schooling processes and ethnic/indigenous students’ socio-cultural backups. School culture, pedagogy, and classroom management have not well fostered thewillingness to nurture and support cultural competence, interconnectedness, inter-reciprocity, and mutual understanding to welcome the unwelcoming in school. The article, therefore, warrants an immediate initiation to bringing an entire improvement in school culture in a way that addresses every need and expectation of linguistically, culturally, ethnically, economically, geographically, and religiously diverse children.